An Adolescent with Possible Arrhythmogenic Right Ventricular Dysplasia and Long QT Syndrome: Evaluation and Management. Issue 1 (24th January 2013) - Tisma‐Dupanovic, Svjetlana; Wagner, Jonathan B.; Shah, Sanket; Huang, David T.; Moss, Arthur J.
<x xml:space="preserve">Abstract</x> We describe a unique presentation of arrhythmogenic right ventricular dysplasia (ARVD) in a 14‐year‐old Caucasian male who was additionally diagnosed with long QT syndrome (LQTS). Genetic testing eventually confirmed the diagnosis of both ARVD and LQTS, which combined, to our knowledge, has not been reported in the literature.